(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
PT. Denkindo Central Elektrik applies powder coating technology in its electrical panel production, where stable oven heating is essential. Manual regulation often leads to LPG freezing and unstable combustion, increasing fuel consumption. To address this, an automatic temperature control system was developed using a DS18B20 sensor, ESP32 microcontroller, ON/OFF relay, and water heating support. Calibration against a water thermometer showed an average error of 1.96%, ensuring accuracy. The system was tested over 45-minute production cycles with 3-minute intervals, and LPG consumption measured by cylinder weight. Results showed LPG temperature dropped to 23.2 °C under manual operation but was maintained at 37–40 °C with control, preventing freezing risk. While oven performance to reach 180 °C was similar (24 minutes), LPG consumption decreased from 3.65 to 1.85 kg per cycle, saving 1.8 kg (Rp36,000). With an investment of Rp1,500,000, the break-even point is reached after 42 cycles. These findings indicate improved safety, efficiency, and economic benefit, though validation was limited to two cycles.